2017
DOI: 10.3892/or.2017.5634
|View full text |Cite
|
Sign up to set email alerts
|

PRKDC regulates chemosensitivity and is a potential prognostic and predictive marker of response to adjuvant chemotherapy in breast cancer patients

Abstract: DNA-dependent kinase catalytic subunit (DNA-PKcs) is a critical component of DNA repair machinery and is found to be up- or down-regulated in different cancer types. However, its clinical significance in breast cancer remains unclear. To this end, quantitative PCR was performed to measure PRKDC expression level in 59 pairs of breast cancer tissues and the non-tumor adjacent tissues (NATs). The correlation between PRKDC expression and overall survival (OS) as well as the prognostic value of PRKDC were analyzed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 32 publications
2
29
0
Order By: Relevance
“…According to recent studies, gene CCNB1 is a prognostic biomarker for certain subtypes of breast cancer and it is closely associated with hormone therapy resistance [20]. It has also been reported in the literature that the PRKDC regulates chemosensitivity and is a potential prognostic and predictive marker of response to adjuvant chemotherapy in breast cancer patients [21]. Our findings about several other genes including CHEK2 and CDC7 also confirmed some existing reports [22,23].…”
Section: A Genomic Applicationsupporting
confidence: 89%
“…According to recent studies, gene CCNB1 is a prognostic biomarker for certain subtypes of breast cancer and it is closely associated with hormone therapy resistance [20]. It has also been reported in the literature that the PRKDC regulates chemosensitivity and is a potential prognostic and predictive marker of response to adjuvant chemotherapy in breast cancer patients [21]. Our findings about several other genes including CHEK2 and CDC7 also confirmed some existing reports [22,23].…”
Section: A Genomic Applicationsupporting
confidence: 89%
“…Similar to the gene mutation profile, HR and NHEJ had a significant gene amplification profile. Previous studies demonstrated that DSB repair pathway genes were over-expressed in cancers and high expression of these genes was associated with cancer development and resistance to chemotherapy and radiotherapy (8,10,11,25,26,47,48). However, how altered DSB repair pathways contribute to ESCC is much less explored.…”
Section: Discussionmentioning
confidence: 99%
“…Up-regulation of DDR pathways are linked to cause resistance to DNA-damaging radiotherapy and chemotherapy. Especially, activation of DSB repair genes is one of the reasons for cancer radio-and chemo-resistance (4)(5)(6)(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…For RNA-seq data for the TMZ-sensitive LN229 cells ( Figure 5 ), when comparing combined TMZ + OKN to UT treatments ( Figure 5 A ), an interesting downregulated gene includes PODXL (a marker for gastric cancer [53] ), and interesting upregulated genes include TRIB3 (induces apoptosis and reverses resistance to chemotherapy in hepatic carcinoma cells [54] ) and CHAC1 (enhances glioma apoptosis [55] ). When comparing combined TMZ + OKN treatment to TMZ alone ( Figure 5 B ), interesting downregulated genes are IGR1 (associated with shorter disease-free survival in patients whose tumors are ER positive and HER2 positive [56] ; IGF1R signaling pathway is very relevant in drug resistance [57] ), XIST (increased level associated with shorter survival and poorer prognosis [58] ), and PRKDC (prognostic biomarker for chemoresistance in breast cancer patients [59] ). Interesting upregulated genes include ZC3H12A (crucial negative regulator of inflammation [60] ) and RN7SK (potential antiproliferative and tumor-suppressive function [61] ).…”
Section: Discussionmentioning
confidence: 99%